All-solid-state battery
By setting insulating sheets and adhesive sheets in all solid batteries to form gaps, the problem of increasing internal resistance caused by gas sealing during assembly is solved, and the battery performance and safety improvement are achieved.
Patent Information
- Application Number
- CN202380063448.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-09-05
- Publication Date
- 2025-04-11
AI Technical Summary
When assembling the all-solid battery, gases such as atmosphere and trace amounts of water are sealed together with the laminated body, resulting in a deterioration of the bonding between the laminated body and the conductive layer, an internal resistance increases, and a toxic gas such as hydrogen sulfide may be generated.
By providing an insulating sheet and an adhesive sheet in an all-solid battery, a gap is formed to connect the laminated body and the outer body to avoid gas sealing, thereby suppressing the increase in internal resistance.
The internal resistance between the laminated body and the current collector is effectively suppressed, the battery capacity is reduced, and the generation of toxic gas is reduced.
Smart Images

Figure CN119816981A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an all-solid-state battery.
[0002] This application claims priority based on Japanese Patent Application No. 2022-140495 filed in Japan on September 5, 2022, and the contents are cited herein. Background Art
[0003] In recent years, electronic technology has developed significantly, achieving small, light, thin, and multifunctional portable electronic devices. As a result, there is a strong desire for batteries, which are used as power sources for electronic devices, to be small, light, thin, and have improved reliability. Due to this situation, all-solid batteries using solid electrolytes as electrolytes disclosed in Patent Documents 1 and 2 have attracted much attention.
[0004] The all-solid battery disclosed in Patent Document 1 has a plurality of component parts in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are stacked in sequence, and the two end faces in the stacking direction of the plurality of component parts are in contact with the first conductive layer and the second conductive layer extending in the in-plane direction, respectively. In the all-solid battery disclosed in Patent Document 1, the side surface of the component part (laminate) is surrounded by a frame, and the end face in the stacking direction is in contact with the conductive layer as described above. That is, the component part of the all-solid battery disclosed in Patent Document 1 is surrounded by other components on the entire surface.
[0005] The all-solid battery disclosed in Patent Document 2 has a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, and a collector plate that clamps them in the stacking direction, and is provided with a cylindrical insulating frame that is closely arranged on the side of the collector plate. The cylindrical insulating frame is used in the manufacture of the all-solid battery, and the materials that will become the positive electrode layer, the negative electrode layer, and the solid electrolyte layer are stored inside the cylindrical insulating frame, and the all-solid battery is manufactured by pressurizing them in the stacking direction. Patent Document 2 discloses that at this time, the materials of the positive electrode layer and the negative electrode layer enter between the collector plate and the insulating frame at the end of the stacking direction, and ensure the airtightness between the collector plate and the insulating frame.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-76182
[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-159635 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] However, when assembling the all-solid batteries disclosed in Patent Documents 1 and 2, even when the assembly is performed in a dry room, the atmosphere, a trace amount of water (water vapor), and other gases may be sealed together with the stacked body by other members.
[0012] If the atmosphere is sealed together with the stack by other components, air will accumulate between the stack and the conductive layer, and the interface between the stack and the conductive layer will open, thereby deteriorating the bonding between the stack and the conductive layer, and increasing the internal resistance between the stack and the collector. In addition, there is also a concern that the battery capacity will decrease.
[0013] When water is sealed together with the stack, it is possible to react with the sulfide solid electrolyte or halide solid electrolyte contained in the solid electrolyte layer during charging and discharging to produce hydrogen sulfide or hydrogen chloride gas. The generation of such gas is significant at high temperatures. If byproduct gases such as hydrogen sulfide or hydrogen chloride are generated in a confined space, the bonding between the stack and the collector is deteriorated, and the internal resistance between the stack and the collector is likely to increase. In addition, it is necessary to avoid the generation of toxic hydrogen sulfide.
[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an all-solid-state battery capable of suppressing an increase in the internal resistance between a stacked body and a current collector.
[0015] Means for solving technical problems
[0016] (1) An all-solid-state battery of one embodiment of the present invention comprises: an outer casing; and arranged in the outer casing: a stacked body, which is stacked with a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence; a positive electrode collector and a negative electrode collector sandwiching the stacked body in the stacking direction; an insulating sheet, which is located between the positive electrode collector and the negative electrode collector and is located in the in-plane direction relative to the stacked body; a first adhesive sheet, which is located between the insulating sheet and the positive electrode collector and bonds the insulating sheet and the positive electrode collector at least in part; and a second adhesive sheet, which is located between the insulating sheet and the negative electrode collector and bonds the insulating sheet and the negative electrode collector at least in part, and the stacked body is connected to the outer casing.
[0017] (2) In the all-solid-state battery of (1) above, at least one gap may be formed in the insulating unit formed by the first adhesive sheet, the insulating sheet, and the second adhesive sheet, and the stacked body and the outer casing may be connected via the gap.
[0018] (3) In the all-solid-state battery of (1) or (2) above, the void may be formed in at least one of the first adhesive sheet and the second adhesive sheet.
[0019] (4) In the all-solid-state battery according to any one of (1) to (3) above, two of the gaps may be formed in the insulating unit, and the two gaps may be provided at positions that do not overlap when viewed from above in the stacking direction.
[0020] (5) In the all-solid-state battery according to any one of (1) to (4) above, four gaps may be formed in the insulating unit, and the four gaps may be arranged at positions that do not overlap when viewed from above in the stacking direction.
[0021] (6) In the all-solid-state battery according to any one of (1) to (5) above, the width of the void may be smaller than the minimum width when the stack is viewed from above in the stacking direction.
[0022] (7) In the all-solid-state battery according to any one of (1) to (6) above, the first adhesive sheet and the second adhesive sheet may be provided along an end surface of the insulating sheet on a side close to the stack.
[0023] (8) In the all-solid-state battery according to any one of (1) to (7) above, the gap may be formed at a position overlapping the first adhesive sheet, the insulating sheet, and the second adhesive sheet when viewed from above in the stacking direction.
[0024] (9) In the all-solid-state battery of any one of (1) to (8) above, the first adhesive sheet may include a plurality of adhesive sheets spaced apart from each other in different directions relative to the stack, and the second adhesive sheet may include a plurality of adhesive sheets spaced apart from each other in different directions relative to the stack.
[0025] (10) In the all-solid-state battery of any one of (1) to (9) above, the distance between the positive electrode collector and the negative electrode collector in the region overlapping with the first adhesive sheet may be smaller than the distance between the positive electrode collector and the negative electrode collector in the region overlapping with the stack.
[0026] (11) In the all-solid-state battery of any one of (1) to (10) above, the first adhesive sheet and the insulating sheet may surround the stack in the in-plane direction, and when observed from the stacking direction of the stack, the shape of the inner periphery of the insulating sheet on the side close to the stack is similar to or identical to the shape of the inner periphery of any one of the first adhesive sheet and the second adhesive sheet on the side close to the stack.
[0027] (12) In the all-solid-state battery of any one of (1) to (11) above, the first adhesive sheet, the second adhesive sheet and the insulating sheet may surround the stack in the in-plane direction, and when observed from the stacking direction of the stack, the size of the inner circumference of the stack surrounded by the first adhesive sheet and the second adhesive sheet is less than the size of the inner circumference of the stack surrounded by the insulating sheet.
[0028] (13) In the all-solid-state battery of the above embodiment, the relationship between the thickness T40 of the insulating sheet and the total thickness T45 of the insulating sheet, the first adhesive sheet, and the second adhesive sheet may satisfy the following formula [1]:
[0029] 0.3≤T40 / T45≤0.96……[1].
[0030] (14) In the all-solid-state battery of the above embodiment, the ratio T51 / T52 of the thickness T51 of the first adhesive sheet to the thickness T52 of the second adhesive sheet may satisfy the relationship of the following formula [2]:
[0031] 0.15≤T51 / T52≤7……[2].
[0032] (15) In the all-solid-state battery of the above aspect, the thickness T51 of the first adhesive sheet may be 4 to 110 μm.
[0033] (16) In the all-solid-state battery of the above aspect, the thickness T52 of the second adhesive sheet may be 4 to 110 μm.
[0034] Effects of the Invention
[0035] According to the present invention, it is possible to provide an all-solid-state battery capable of suppressing an increase in the internal resistance between a stacked body and a current collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a perspective view showing an example of the structure of an all-solid-state battery according to one embodiment of the present invention.
[0037] Figure 2 Yes Figure 1 Cross-sectional view of the all-solid-state battery cut along the stacking direction.
[0038] Figure 3 Observed from the stacking direction Figure 1 Plan view of an all-solid-state battery.
[0039] Figure 4 This is a cross-sectional view of the all-solid-state battery according to the embodiment of the present invention cut along the stacking direction.
[0040] Figure 5This is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction.
[0041] Figure 6 Observed from the stacking direction Figure 5 Plan view of an all-solid-state battery.
[0042] Figure 7 This is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction.
[0043] Figure 8 Observed from the stacking direction Figure 7 Plan view of an all-solid-state battery.
[0044] Fig. 9 (a) and Fig. 9 (b) is observed from the stacking direction Figure 3 A plan view of a modified example of an all-solid-state battery.
[0045] Fig.10 This is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction.
[0046] Fig.11 Observed from the stacking direction Fig.10 Plan view of an all-solid-state battery.
[0047] Fig.12 This is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction.
[0048] Fig.13 Observed from the stacking direction Fig.12 Plan view of an all-solid-state battery.
[0049] Fig.14 (a)~ Fig.14 (c) is observed from the stacking direction Fig.13 A plan view of a modified example of an all-solid-state battery.
[0050] Fig.15 (a)~ Fig.15 (c) is a plan view of an all-solid-state battery according to another embodiment of the present invention as viewed from the stacking direction.
[0051] Fig.16 (a)~ Fig.16 (c) is a plan view of an all-solid-state battery according to another embodiment of the present invention as viewed from the stacking direction.
[0052] Fig.17 The charge and discharge curves of Example 1 and Comparative Example 1 are shown.
[0053] Fig.18 (a) and Fig.18 (b) shows the conditions of the all-solid batteries of Example 1 and Comparative Example 1 after the battery capacity test and the internal resistance test.
[0054] Fig.19 The charge and discharge curves of Example 2 and Comparative Example 2 are shown.
[0055] Explanation of symbols:
[0056] 10: laminate, 11: positive electrode active material layer, 12: solid electrolyte layer, 13: negative electrode active material layer, 14, 16: lead, 15: current collector, 15A: positive electrode current collector, 15B: negative electrode current collector, 20: outer casing, 22: metal foil, 24: resin layer, 40, 40A, 40C, 40H, 40O: insulating sheet, 45: insulating unit, 50, 50A, 50B, 50G, 50H, 50L: adhesive Connecting sheet, 51A, 51B, 51G: first adhesive sheet, 52A, 52C, 52G: second adhesive sheet, 90: energy storage element, 100A, 100B, 100C, 100D, 100E, 100F, 100G, 100H, 100I, 100J, 100K, 100L, 100M: all-solid-state battery, A: gap, H40: through hole (of insulating sheet), H50: through hole (of adhesive sheet). DETAILED DESCRIPTION
[0057] Hereinafter, an example of an embodiment of the present invention will be described in detail with reference to the accompanying drawings. In addition, the accompanying drawings used in the following description may enlarge the characteristic parts for convenience in order to facilitate understanding of the characteristics of the present invention. Therefore, the dimensional ratios of the various components may be different from the actual ones.
[0058] [All-solid-state battery]
[0059] Figure 1 This is a perspective view showing an example of the structure of an all-solid-state battery according to one embodiment of the present invention. Figure 2 Yes Figure 1 Cross-sectional view of the all-solid-state battery cut along the stacking direction. Figure 3 Observed from the stacking direction Figure 1 Plan view of an all-solid-state battery.
[0060] Figure 1 to Figure 3 The all-solid-state battery 100A shown includes an outer casing 20 and an electric storage element 90 accommodated in an accommodation space K within the outer casing 20. Figure 1 In FIG. 1 , for easy understanding, a state immediately before the power storage element 90 is housed in the exterior body 20 is shown.
[0061] {External body}
[0062] The outer casing 20 includes, for example, a metal foil 22 and resin layers 24 laminated on both surfaces of the metal foil 22 (see Figure 2 ). The outer body 20 is a metal laminated film formed by coating a metal foil 22 on both sides with a polymer film (resin layer). The metal foil 22 is, for example, aluminum foil. The resin layer 24 is, for example, a polymer film such as polypropylene. The resin layer 24 may be different on the inside and outside. For example, as the outer resin layer, a polymer with a high melting point, such as polyethylene terephthalate (PET), polyamide (PA), etc., can be used, and as the inner resin layer, a resin layer with high heat resistance, oxidation resistance, and reduction resistance, such as polyethylene (PE) and polypropylene (PP), can be used.
[0063] {Electrical storage element}
[0064] The storage element 90 includes a laminate 10, a positive electrode collector 15A, a negative electrode collector 15B, an insulating sheet 40, a first adhesive sheet 51A, and a second adhesive sheet 52A. Hereinafter, when the positive electrode collector 15A and the negative electrode collector 15B are not distinguished, they are sometimes simply referred to as the collector 15. In addition, when the first adhesive sheet 51A and the second adhesive sheet 52A are not distinguished, they are sometimes simply referred to as the adhesive sheet 50A. In addition, in the plan view, sometimes only the symbol 50A is indicated, but the configuration in the laminate structure is as shown in the cross-sectional view. The first adhesive sheet 51A, the insulating sheet 40A, and the second adhesive sheet 52A constitute the insulating unit 45A.
[0065] <Current Collector>
[0066] The positive electrode current collector 15A and the negative electrode current collector 15B each extend in a plane direction intersecting the z direction. The positive electrode current collector 15A and the negative electrode current collector sandwich the stack 10 in the z direction. Figure 2 and Figure 3 In FIG. 1 , the width of the current collector 15 in the x direction is represented by W15 , and the length of the current collector 15 in the y direction is represented by L15 .
[0067] The positive electrode collector 15A and the negative electrode collector 15B are made of, for example, a material with high electrical conductivity. The positive electrode collector 15A and the negative electrode collector 15B are made of, for example, a metal such as silver, palladium, gold, platinum, aluminum, copper, nickel, titanium, stainless steel, or an alloy thereof, or a conductive resin. The positive electrode collector 15A and the negative electrode collector 15B may be made of the same material or different materials. Figure 2 and Figure 3 In FIG. 1 , an example is shown in which the positive electrode current collector 15A and the negative electrode current collector 15B have the same size, but they may be different in size.
[0068] <Laminate>
[0069] In the stack 10, the positive electrode active material layer 11, the solid electrolyte layer 12 and the negative electrode active material layer 13 are stacked in sequence in the z direction. The stack 10 is arranged between the positive electrode collector 15A and the negative electrode collector 15B. The stack 10 is received in the through holes H40 and H50 described later, for example, in the in-plane direction of the positive electrode active material layer 11. In this embodiment, the space corresponding to the through hole H40 and the through hole H50 when viewed from above is sometimes referred to as a receiving portion. The stack 10 is connected to the outer body 20. The stack 10 and the outer body 20 are connected, for example, via the gap A formed in the insulating unit 45A described later. That is, the gap A can be said to be a path connecting multiple gaps to each other.
[0070] The planar shape of the laminate 10 is, for example, circular. In the present embodiment, the outer dimensions of the laminate 10 when planarly viewed from the z direction are represented by D10, and the thickness of the laminate 10 in the z direction is represented by T10.
[0071] The stack 10 exchanges electrons with the positive electrode current collector 15A and the negative electrode current collector 15B, and exchanges lithium ions through the solid electrolyte layer 12. The stack 10 exchanges electrons and lithium ions, and the all-solid battery 100A is charged or discharged.
[0072] (Positive Electrode Active Material Layer)
[0073] The positive electrode active material layer 11 is located on the positive electrode collector 15A side of the solid electrolyte layer 12. The positive electrode active material layer 11 contains a positive electrode active material and may contain a conductive auxiliary agent, a binder, and a solid electrolyte described later as necessary.
[0074] The positive electrode active material contained in the positive electrode active material layer 11 is, for example, a lithium-containing transition metal oxide, a transition metal fluoride, a polyanion, a transition metal sulfide, a transition metal oxyfluoride, a transition metal oxysulfide, or a transition metal oxynitride.
[0075] The positive electrode active material is not particularly limited as long as it can reversibly release and absorb lithium ions, and extract and insert lithium ions. For example, a positive electrode active material used in a known lithium ion secondary battery can be used.
[0076] The positive electrode active material is specifically, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), spinel lithium manganese oxide (LiMn2O4), and lithium nickel oxide (LiNiO2). x Co y Mn z M aComposite metal oxides represented by O2(x + y + z + a = 1, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ a ≤ 1, where M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compounds (LiV2O 5、 Li3V2(PO4)3, LiVOPO4), olivine-type LiMPO4 (where M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, V, Nb, Ti, Al, Zr), lithium titanate (Li4Ti5O 12 ), LiNi x Co y Al z O2(0.9 < x + y + z < 1.1) and other composite metal oxides.
[0077] In addition, if a negative electrode active material doped with metallic lithium or lithium ions is previously disposed on the negative electrode, it is also possible to use a positive electrode active material that does not contain lithium starting from the start of discharging the battery. Examples of such positive electrode active materials include lithium-free metal oxides (MnO2, V2O5, etc.), lithium-free metal sulfides (MoS2, etc.), lithium-free fluorides (FeF3, VF3, etc.).
[0078] (Negative electrode active material layer)
[0079] The negative electrode active material layer 13 is located on the side of the negative electrode current collector 15B of the solid electrolyte layer 12. The negative electrode active material layer 13 contains a negative electrode active material and may contain, as needed, a conductive assistant, a binder, and a solid electrolyte described later.
[0080] The negative electrode active material contained in the negative electrode active material layer 13 may be any compound that can occlude and release mobile ions, and known negative electrode active materials used in lithium ion secondary batteries can be used. Examples of the negative electrode active material are alkali metal monomers, alkali metal alloys, carbon materials such as graphite (natural graphite, artificial graphite), carbon nanotubes, hardly graphitizable carbon, easily graphitizable carbon, low-temperature fired carbon, metals such as aluminum, silicon, tin, germanium and their alloys that can combine with metals such as alkali metals, SiO x (0 < x < 2), oxides such as iron oxide, titanium oxide, tin dioxide, and lithium metal oxides such as lithium titanate (Li4Ti5O 12 ).
[0081] The conductive aid that can be included in the positive electrode active material layer 11 and the negative electrode active material layer 13 is not particularly limited as long as it can improve the electronic conductivity of the positive electrode active material layer 11 and the negative electrode active material layer 13, and a known conductive aid can be used. Examples of the conductive aid include carbon materials such as graphite, carbon black, graphene, and carbon nanotubes, metals such as gold, platinum, silver, palladium, aluminum, copper, nickel, stainless steel, and iron, conductive oxides such as ITO, or mixtures thereof. The conductive aid can be in the form of powder or fiber.
[0082] (Adhesive)
[0083] The binder joins the positive electrode collector 15A and the positive electrode active material layer 11 , the negative electrode collector 15B and the negative electrode active material layer 13 , the positive electrode active material layer 11 and the negative electrode active material layer 13 and the solid electrolyte layer 12 , various materials constituting the positive electrode active material layer 11 , and various materials constituting the negative electrode active material layer 13 .
[0084] The binder is used within the range that the functions of the positive electrode active material layer 11 and the negative electrode active material layer 13 are not lost. The binder can be any one as long as it can perform the above-mentioned bonding, and examples thereof include fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). Furthermore, in addition to the above, as a binder, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, etc. can also be used. In addition, as a binder, a conductive polymer with electronic conductivity and an ion conductive polymer with ion conductivity can also be used. As a conductive polymer with electronic conductivity, for example, polyacetylene can be mentioned. In this case, the binder also plays the role of a conductive auxiliary agent particle, so the conductive auxiliary agent may not be added. As an ion conductive polymer with ion conductivity, for example, an ion conductive polymer that conducts lithium ions can be used, and examples thereof include a polymer compound (polyether polymer compounds such as polyethylene oxide and polypropylene oxide, polyphosphazene, etc.) and a monomer thereof. LiClO4, LiBF4, LiPF 6、 Lithium salts such as LiTFSI and LiFSI or alkali metal salts with lithium as the main component are composited, etc. As the polymerization initiator used in the composite, for example, it is a photopolymerization initiator or a thermal polymerization initiator suitable for the above-mentioned monomer. As the characteristics required for the adhesive, oxidation / reduction resistance and good adhesion can be cited. If the adhesive is not required, it is not necessary to contain the adhesive.
[0085] The content of the binder in the positive electrode active material layer 11 is not particularly limited, but is preferably 0.5 to 30% by volume of the positive electrode active material layer from the viewpoint of reducing the resistance of the positive electrode active material layer 11. In addition, from the viewpoint of increasing the energy density, the content of the binder in the positive electrode active material layer 11 is preferably 0% by volume.
[0086] The content of the binder in the negative electrode active material layer 13 is not particularly limited, but is preferably 0.5 to 30% by volume of the negative electrode active material layer from the viewpoint of reducing the resistance of the negative electrode active material layer 13. In addition, from the viewpoint of increasing the energy density, the content of the binder in the negative electrode active material layer 13 is preferably 0% by volume.
[0087] (Solid electrolyte layer)
[0088] The solid electrolyte layer 12 is located between the positive electrode active material layer 11 and the negative electrode active material layer 13. The solid electrolyte layer 12 contains a solid electrolyte. The solid electrolyte is a substance (for example, particles) that can move ions by an electric field applied from the outside. In addition, the solid electrolyte layer is an insulator that hinders the movement of electrons.
[0089] The solid electrolyte contains lithium, for example. The solid electrolyte may be a halide material such as a composition represented by the following formula [3], Li 3.25 Ge 0.25 P 0.75 Any sulfide material such as S4.
[0090] A a E b G c X d ……[3]
[0091] (In formula [3], A is at least one element selected from Li and Cs, E is at least one element selected from Al, Sc, Y, Zr, Hf, and lanthanide elements, and G is at least one element selected from OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3、PO4、P2O7、P3O 10 , SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, X is at least one element selected from F, Cl, Br, I, 0.5≤a<6, 0 <b<2、0≤c≤6、0≤d≤6.1。)
[0092] The solid electrolyte may be, for example, a Thio-LISICON (lithium sulfide fast ion conductor) type compound or a glass compound. 3.25 Ge 0.25 P 0.75S4 and Li3PS4 are examples of Thio-LISICON type compounds. Li2S-P2S5 is an example of a glass compound. In addition, any material can be used as the solid electrolyte as long as it can be used in a powder forming method of a pressed powder type. The solid electrolyte may contain one or more of these compounds.
[0093] The solid electrolyte layer 12 may also contain substances other than the solid electrolyte material. For example, the solid electrolyte layer 12 may contain sulfides or halides of alkali metal elements, sulfides or halides of transition metal elements, etc. In addition, the solid electrolyte layer 12 may also have a binder. The binder is the same as described above.
[0094] (Insulation Sheet)
[0095] The insulating sheet 40 is located between the positive electrode current collector 15A and the negative electrode current collector 15B, and is located in the in-plane direction relative to the laminate 10. The insulating sheet 40 extends, for example, in the xy plane intersecting the z direction. The insulating sheet 40 surrounds the laminate 10, for example. The insulating sheet 40 is, for example, a single insulating film, or a plurality of insulating films may be overlapped. When the insulating sheet 40 is composed of a plurality of overlapping insulating films, for example, the side surfaces are fixed by tape or the like. Figure 2 In the figure, T40 is used to represent the thickness of the insulating sheet 40. Figure 2 and Figure 3 In FIG. 5 , W40 represents the width in the x direction of the insulating sheet 40, and L40 represents the length in the y direction of the insulating sheet 40. The thickness T40 of the insulating sheet 40 is, for example, 50 to 250 μm, preferably 90 to 210 μm, and more preferably 95 to 160 μm.
[0096] The insulating sheet 40 is, for example, an insulating resin, and a known insulating material can be used. The insulating sheet 40 is preferably an insulating film that is easy to process. The insulating sheet 40 is made of, for example, polyethylene terephthalate, polypropylene, polyimide, or PTFE.
[0097] The insulating sheet 40 has a through hole H40 penetrating in the z direction, for example, inside thereof. The laminated body 10 is accommodated inside the through hole H40, for example.
[0098] The shape of the through hole H40 when viewed from the z direction is, for example, a shape similar to that of the laminated body 10. Hereinafter, the through hole H40 and the laminated body 10 are described as circular shapes.
[0099] The size of the through hole H40 when viewed from the z direction is larger than the size of the laminate 10. That is, the inner dimension d40 of the through hole H40 when viewed from the z direction is larger than the outer dimension D10 of the laminate 10. Therefore, the insulating sheet 40 is arranged at a distance from the laminate 10, and there is a space R between the insulating sheet 40 and the laminate 10. Figure 3 In FIG. 1 , the distance between the insulating sheet 40 and the laminate 10 is shown to be constant at any position, but the distance between the insulating sheet 40 and the laminate 10 may be different depending on the position.
[0100] (Adhesive Sheet)
[0101] As described above, the adhesive sheet 50A includes a first adhesive sheet 51A and a second adhesive sheet 52A. The first adhesive sheet 51A is located between the insulating sheet 40A and the positive electrode collector 15A, and bonds the insulating sheet 40A and the positive electrode collector 15A at least in a portion. The first adhesive sheet 51A, for example, bonds the main surface S40A of the insulating sheet 40A to the main surface S15A of the positive electrode collector 15A. The second adhesive sheet 52A is located between the insulating sheet 40A and the negative electrode collector 15B, and bonds the insulating sheet 40A and the negative electrode collector 15B at least in a portion. The second adhesive sheet 52B bonds the main surface S40B of the insulating sheet 40 to the main surface S15B of the negative electrode collector 15B.
[0102] The adhesive sheet 50A is provided, for example, along the end surface of the insulating sheet 40A on the side close to the laminate 10. In the present embodiment, the configuration described as the feature of the adhesive sheet 50A is a feature common to the first adhesive sheet 51A and the second adhesive sheet 52A.
[0103] The adhesive sheet 50A is, for example, a double-sided tape, an adhesive, or a thermal adhesive sheet.
[0104] A specific example of a double-sided tape is a double-sided tape whose adhesive layer is any one of rubber, acrylic, and silicone materials, and whose substrate is any one of non-woven fabrics, films, foams, cloth, and paper, or a double-sided tape without a substrate consisting only of the adhesive layer. A specific example of an adhesive is an adhesive such as vinyl resin, styrene resin, rubber, and vinyl resin. A specific example of a thermal adhesive sheet is a thermal adhesive sheet of epoxy resin such as FB-ML80 / FB-ML4 (manufactured by Nitto Denko Corporation).
[0105] The configuration and shape of the adhesive sheet 50A correspond to the configuration and shape of the collector 15 and the stack 10, for example. The adhesive sheet 50A is provided with a through hole H50 for accommodating the stack 10, for example. The adhesive sheet 50A surrounds the substantially entire circumference of the stack 10 using the through hole H50, for example. The first adhesive sheet 51A is, for example, spaced apart from the stack 10 and surrounds the entire circumference of the stack 10. The second adhesive sheet 52A is, for example, formed with at least one gap A, and the stack 10 and the outer body 20 are connected via the gap A. That is, the gap A serves as an exhaust path for exhausting the gas near the stack 10 to the area spaced apart from the stack 10. The gap A, when viewed from the stacking direction, is, for example, linear, and is provided in a manner connecting the through hole H50 and the end face of the second adhesive sheet 52A.
[0106] The width of the gap A formed in the second adhesive sheet 52A is preferably smaller than the width when the stacked body 10 is viewed from the z direction, and more preferably smaller than the minimum width of the stacked body 10. The width of the gap A in the second adhesive sheet 52A is the length in a direction perpendicular to the length direction of the gap A, and is Figure 3 The width of the gap A in the x direction of the example shown. By making the width of the gap A of the second adhesive sheet 52A smaller than the width when the stack 10 is viewed from the z direction, it is easy to obtain the effect of suppressing the positional deviation in the in-plane direction of the stack 10. In the all-solid battery 100A, the shape of the gap A when viewed from the y direction is defined by, for example, the positive electrode collector 15A, the second adhesive sheet 52A, and the insulating sheet 40.
[0107] The gap A can be formed with respect to the second adhesive sheet 52A by, for example, punching using a die together with the through hole H50. When viewed from the stacking direction, the shape of the inner periphery of the insulating sheet 40 on the side close to the stack 10 can be similar or congruent to the shape of the inner periphery of the side close to the stack 10 of either the first adhesive sheet 51A or the second adhesive sheet 52A.
[0108] Furthermore, when viewed from the stacking direction, the dimensions of the first adhesive sheet 51A and the second adhesive sheet 52A around the inner periphery of the stacked body 10 may be smaller than the dimensions of the insulating sheet 40 around the inner periphery of the stacked body 10. That is, the inner dimension d40 may be smaller than the inner dimension d50.
[0109] The thickness of the first adhesive sheet 51A is set to T51, and the thickness of the second adhesive sheet 52A is set to T52. Hereinafter, when the thicknesses T51 and T52 are not particularly distinguished, they are simply referred to as the thickness T50 of the adhesive sheet 50A. The thickness T50 of the adhesive sheet 50A in the stacking direction is, for example, 1 to 150 μm, preferably 4 to 110 μm, and more preferably 20 to 105 μm. The ratio T51 / T52 of the thickness T51 of the first adhesive sheet 51A to the thickness T52 of the second adhesive sheet 52A is, for example, 0.1 to 10, preferably 0.15 or more and 7 or less, and more preferably 0.9 or more and 3 or less.
[0110] In the overlapping region where the adhesive sheet 50A and the insulating sheet 40 overlap, the total value of the thickness of all the adhesive sheets 50A and the insulating sheet 40 is expressed as the thickness T45. The ratio T45 / T10 of the total thickness T45 of the adhesive sheet 50A and the insulating sheet 40 to the thickness T10 of the stack 10 is, for example, 20 to 100%, preferably 50 to 100%, and more preferably 65 to 95%. That is, the thickness T10 of the stack 10 is preferably greater than the thickness T45 of the insulating unit 45. By adopting such a configuration, the adhesion between the positive electrode collector 15A and the positive electrode active material layer 11 and the adhesion between the negative electrode collector 15B and the negative electrode active material layer 13 can be improved. The ratio T40 / T45 of the thickness T40 of the insulating sheet 40 to the thickness T45 of the insulating unit which is the total thickness of the insulating sheet 40, the first adhesive sheet 51A and the second adhesive sheet 52A is, for example, greater than 0.2 and less than 1.2, preferably greater than 0.3 and less than 0.96, and more preferably greater than 0.31 and less than 0.7.
[0111] The spacing between the positive electrode collector 15A and the negative electrode collector 15B depends on, for example, the thickness of the structure sandwiched between them. For example, the area where the stack 10 overlaps with the positive electrode collector 15A and the negative electrode collector 15B in the z direction is called the first area, and the area where the adhesive sheet 50A overlaps with the insulating sheet 40 in the z direction is called the second area. In this case, the spacing between the positive electrode collector 15A and the negative electrode collector 15B in the first area (hereinafter referred to as the first spacing) is wider than the spacing between the positive electrode collector 15A and the negative electrode collector 15B in the second area (hereinafter referred to as the second spacing). The ratio of the second spacing to the first spacing is the same as the ratio T45 / T10 of the total thickness T45 of the layered insulating unit 45 in the second area to the thickness T10 of the stack 10.
[0112] In addition, for example, when the total thickness T45 in the second region is smaller than the thickness T10 of the stack 10, the second interval is smaller than the first interval. In such a structure, for example, in the first region, the positive electrode collector 15A and the negative electrode collector 15B are recessed by the stack 10. Thus, by making the total thickness T45 of the adhesive sheet 50A and the insulating sheet 40 within this range relative to the thickness of the stack 10, it is easy to make the stack 10 and the collector 15 close to each other, it is easy to reduce the internal resistance, and it is easy to suppress the stack from being damaged.
[0113] The distance in the in-plane direction between the adhesive sheet 50A and the laminate 10 may also be different according to each position in the z direction. In this case, the shortest distance in the in-plane direction between the adhesive sheet 50A and the laminate 10 is referred to as the distance da. The distance da between the internal dimension d50 and the external dimension D10 is, for example, 0 mm or more and 1 mm or less, or 0.1 mm or more and 1 mm or less, or 0.5 mm or more and 1 mm or less. The ratio D10 / d50 between the external dimension D10 of the laminate 10 and the internal dimension d50 of the through hole H50 is, for example, 0.9 or more and 1 or less, or 0.9 or more and 0.97 or less. In this way, by making the internal dimension d50 of the adhesive sheet 50A correspond to the external dimension D10 of the laminate 10, it is easy to suppress the positional deviation of the laminate 10.
[0114] Next, an example of a method for manufacturing the all-solid-state battery of the present embodiment is described. The all-solid-state battery of the present embodiment is manufactured by a powder molding method.
[0115] (Step of forming a laminate)
[0116] First, prepare a resin retainer having 51 in the center, a lower punch, and an upper punch. In order to achieve good formability, a metal retainer made of die steel may be used instead of the resin retainer. The diameter of the through hole of the resin retainer is a desired size as the external dimension D10 of the stack 10, and can be formed to a size that allows the above-mentioned lower punch and upper punch to be inserted therein. The lower punch is inserted from below the through hole of the resin retainer, and a powdered solid electrolyte is injected from the opening side of the resin retainer. Next, an upper punch is inserted on top of the injected powdered solid electrolyte, placed on a press, and pressurized to form a solid electrolyte layer 12.
[0117] Next, the upper punch is temporarily removed, and the material of the positive electrode active material layer is poured into the upper punch side of the solid electrolyte layer 12. Then, the upper punch is inserted again and pressed to form the positive electrode active material layer 11.
[0118] Next, temporarily remove the lower punch, and throw the material of the negative electrode active material layer onto the lower punch side of the solid electrolyte layer 12. For example, throw the material of the negative electrode active material layer onto the solid electrolyte layer 12 in such a way that the sample is turned upside down and faces the positive electrode active material layer 11. After that, insert the lower punch again and pressurize. Then, as a formal forming, pressurization is performed, for example, with a stronger pressure than the previous pressurization. Thus, a laminated body in which the positive electrode active material layer 11, the solid electrolyte layer 12, and the negative electrode active material layer 13 are stacked in sequence is formed.
[0119] Next, the stacked body 10 is taken out from the resin holder. To take the stacked body 10 out from the resin holder, for example, the upper punch is inserted and pressurized while the lower punch is removed. Alternatively, the lower punch is inserted and pressurized while the upper punch is removed. In this way, the stacked body 10 is obtained.
[0120] (Step of Forming Insulation Unit)
[0121] First, an insulating film having a predetermined shape is prepared. Next, the insulating film is pressurized and cut using a forming die. The shape of the forming die corresponds to the desired through hole H40. The forming die is set at a desired position in the insulating film for forming the through hole H40. In order to cut the insulating film, for example, a punching knife is used. As a punching knife, a Pinnacle knife (Pinnacle is a registered trademark) or the like can be used.
[0122] Next, prepare a double-sided tape for the adhesive sheet. Cut the double-sided tape to form the through hole H50 and the gap A. The adhesive sheet can be cut, for example, by punching in the same way as the through hole H40 is formed in the insulating sheet, or by using a cutting mechanism such as scissors. In this way, a layered insulating unit 45 is obtained in which the first adhesive sheet 51A and the second adhesive sheet 52A are respectively provided on the main surfaces S40A and S40B of the insulating sheet 40.
[0123] (Step of forming positive electrode current collector / negative electrode current collector)
[0124] The positive electrode current collector 15A and the negative electrode current collector 15B are obtained by punching a current collector material into a desired shape using, for example, a punching blade. As the punching blade, for example, a Pinnacle blade (Pinnacle is a registered trademark) or the like can be used.
[0125] (Assembly)
[0126] First, lead 16 and lead 14 as tabs are attached to the outer sides of positive electrode collector 15A and negative electrode collector 15B in the stacking direction, respectively. Lead 16 and positive electrode collector 15A, lead 14 and negative electrode collector 15B can be joined by, for example, ultrasonic welding.
[0127] Next, the insulating sheet 40 is bonded to either the positive electrode collector 15A or the negative electrode collector 15B via the adhesive sheet 50A. Hereinafter, an example in which the insulating sheet 40 is bonded to the positive electrode collector 15A via the adhesive sheet 50A is described, but the insulating sheet 40 may also be bonded to the negative electrode collector 15B.
[0128] Next, the laminated body is housed inside the through holes H40 and H50 of the layered insulating unit 45 using tweezers or the like.
[0129] Next, the insulating sheet 40 is adhered to the negative electrode current collector 15B via the second adhesive sheet 52B so that the laminated body 10 and the layered insulating unit 45 are sandwiched between the positive electrode current collector 15A and the negative electrode current collector 15B.
[0130] Next, one opening of the outer body 20 is left, and the other openings are heat-sealed. After that, the remaining openings may be heat-sealed while the interior of the outer body 20 is evacuated. By heat-sealing while evacuating, the outer body 20 can be sealed in a state where the gas and moisture present in the storage space K are small.
[0131] Through the above steps, the all-solid-state battery 100A of this embodiment can be obtained.
[0132] In addition, the above example of manufacturing an all-solid battery 100A in which a double-sided tape is effectively used as an adhesive sheet is described, but the present invention is not limited to this example. For example, the manufacturing method of the all-solid battery of the present embodiment may also use an adhesive or a thermal adhesive sheet instead of a double-sided tape as an adhesive sheet material. In the case of using an adhesive as an adhesive sheet material, for example, before the insulating sheet 40 is bonded to the collector 15, the adhesive is arranged in a manner overlapping the main surface of the insulating sheet 40. In the case of using a thermal adhesive sheet as an adhesive sheet material, for example, a resin that volatilizes by heating is formed in the region where the gap A is formed, and a thermal adhesive sheet is formed in other regions of the insulating sheet, and the insulating sheet 40 and the adhesive sheet 50A that are sandwiched by the positive electrode collector 15A and the negative electrode collector 15B to accommodate the stack 10 in the through holes H40 and H50 are heated. Thus, the main surface of the collector 15 and the main surface of the insulating sheet 40 are bonded via the adhesive sheet 50A, and the storage element 90 in which the stack 10 and the outer body 20 are connected can be formed. In addition, an example in which the adhesive sheet material is set on the insulating sheet 40 and punched out is described, but it is not limited to this example. The adhesive sheet 50A and the insulating sheet 40 can also be punched out separately and then overlapped. In addition, an example in which the leads 14 and 16 are installed on the outside of the stacking direction of the positive electrode collector 15A and the negative electrode collector 15B is shown, but it is not limited to this example. The leads 14 and 16 can also be installed on the inside of the stacking direction of the positive electrode collector 15A and the negative electrode collector 15B.
[0133] In the all-solid battery 100A of the present embodiment, the first adhesive sheet 51A and the second adhesive sheet 52A are provided between the insulating sheet 40 and the positive electrode collector 15A, and between the insulating sheet 40 and the negative electrode collector 15B, respectively, and the stack 10 and the outer casing 20 are connected, so that it is possible to suppress the air, water vapor and other gases from being sealed together with the stack 10 by the insulating unit 45, the positive electrode collector 15A and the negative electrode collector 15B during assembly. In addition, even if the solid electrolyte in the stack 10 reacts with water and even if a gas such as hydrogen chloride is generated, since the stack 10 and the outer casing 20 are connected, the gas pressure increases in the sealed space where the stack 10 and the positive electrode collector 15A and the negative electrode collector 15B form a part of the outline, and it is possible to suppress the decrease in the adhesion between the stack 10 and the positive electrode collector 15A and the negative electrode collector 15B. Thus, according to the all-solid battery 100A of the present embodiment, the increase in the internal resistance between the stack 10 and the collector 15 can be suppressed. In addition, in the all-solid battery 100A, the insulating sheet 40 and the collector 15 can be bonded by the adhesive sheet 50A, and the decrease in the close contact between the insulating sheet 40 and the collector can be avoided by increasing the above-mentioned air pressure, so that the increase in the above-mentioned internal resistance can be suppressed without using a restraining member that applies pressure in the stacking direction. If the internal resistance of the all-solid battery is excessively increased due to the peeling between the stack 10 and the collector 15, there is a case where the battery capacity is reduced, but in the all-solid battery 100A of the present embodiment, the reduction in battery capacity can also be suppressed.
[0134] In addition, in the all-solid battery 100A, the insulating unit 45 is provided so as to surround the stack 10 in the in-plane direction, and the width of the short side direction of the gap A is smaller than the diameter of the stack 10, so it is particularly easy to suppress the positional deviation in the in-plane direction of the stack 10. Therefore, it is easy to suppress the contact between the positive electrode collector 15A and the negative electrode collector 15B further inside the through holes H40 and H50.
[0135] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the above embodiments, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims. Figure 1 to Figure 3 In the example, a structure in which a gap is formed in the second adhesive sheet 52A is illustrated, but it is sufficient as long as a gap is formed in either the first adhesive sheet 51A or the second adhesive sheet 52A. Alternatively, a structure in which a gap is formed in the first adhesive sheet 51A but not in the second adhesive sheet 52A. In addition, for example, the all-solid battery of the embodiment of the present invention may also be Figures 4 to 16 All-solid-state batteries like those shown in Figure 1. Figures 4 to 16 In, with Figure 1 to Figure 3 The same components of the all-solid-state battery 100A are denoted by the same reference numerals, and description thereof will be omitted.
[0136] Figure 4 This is a cross-sectional view of the all-solid-state battery according to the embodiment of the present invention cut along the stacking direction. Figure 4 The all-solid battery 100B shown in the figure also has a gap formed in the first adhesive sheet 51A, which is different from the all-solid battery 100A. In the all-solid battery 100B, the first adhesive sheet 51B and the second adhesive sheet 52A are provided with gaps of the same shape at overlapping positions when viewed from the z direction.
[0137] Since the gap A that communicates the stacked body 10 and the outer casing 20 is formed between the first adhesive sheet 51B and the second adhesive sheet 52A, hydrogen chloride or hydrogen sulfide near either the positive electrode active material layer 11 or the negative electrode active material layer 13 can be discharged through the gap A.
[0138] In addition, in the above structure, an example is shown in which the configuration of the gap A formed in the first adhesive sheet 51A and the second adhesive sheet 52A is located in an overlapping area when viewed from the z direction, but the two gaps A can also be set at a position that does not overlap when viewed from the z direction. For example, it can also be set at a relative position in the in-plane direction of the stack 10. It is believed that if the two gaps A are set at a position that does not overlap in the in-plane direction, the gas generated in the space R is preferentially exhausted from the gap on the side close to the in-plane direction in the two gaps A, so the gas can be exhausted quickly. That is, by having a plurality of gaps A, the gas is not easy to accumulate in the space R. In addition, in the manufacturing process, when the stack 10 and the positive electrode collector 15A, and the stack 10 and the negative electrode collector 15B are pasted, the positive electrode collector 15A and the negative electrode collector 15B foil are not easy to wrinkle.
[0139] Figure 5 is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction, Figure 6 Observed from the z direction Figure 5 Plan view of an all-solid-state battery. Figure 5 and Figure 6 In the all-solid battery 100C shown, in the insulating unit 45C, only the gap A is provided in the insulating sheet 40C, which is different from the all-solid battery 100A. That is, the all-solid battery 100C does not have a gap. The gap A provided in the insulating sheet 40C connects the stack 10 and the outer body 20. The width of the gap A provided in the insulating sheet 40C is, for example, the same as the width of the gap A provided in the second adhesive sheet 52A in the all-solid battery 100A. In the all-solid battery 100C, the formation of the gap A to the insulating sheet 40C can be performed by, for example, the same means as the formation of the through hole H40 to the insulating sheet 40C.
[0140] Figure 7is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction, Figure 8 Observed from the stacking direction Figure 7 Plan view of an all-solid-state battery. Figure 7 and Figure 8 The all-solid-state battery 100D shown in the figure has a gap A provided at the position where the first adhesive sheet 51B, the second adhesive sheet 52A, and the insulating sheet 40C overlap when viewed from the z direction. Figure 7 and Figure 8 As shown, the all-solid battery can be provided with a gap A in both the adhesive sheet and the insulating sheet. In the case where the insulating sheet 40C, the first adhesive sheet 51B, and the second adhesive sheet 52A are all formed with the gap A as in the all-solid battery 100D, and the gap A is provided at an overlapping position when viewed from the stacking direction, from the perspective of improving manufacturing yield, the formation of the gap is preferably performed by punching out after the adhesive sheet is overlapped with the insulating film. In the all-solid battery 100D, the gap A when viewed from the y direction is defined by the positive electrode collector 15A, the first adhesive sheet 51B, the insulating sheet 40C, the second adhesive sheet 52A, and the negative electrode collector 15B.
[0141] Fig. 9 Observed from the z direction Figure 3 A plan view of a modified example of an all-solid-state battery. Fig. 9 In the all-solid-state battery 100E shown in (a), two gaps A are formed in at least one of the first adhesive sheet, the insulating sheet, and the second adhesive sheet, and the two gaps A are provided at positions that do not overlap when viewed in plan from the z direction. Fig. 9 The all-solid-state battery 100F shown in (b) has four gaps A formed in at least one of the first adhesive sheet, the insulating sheet, and the second adhesive sheet. The four gaps A are provided at positions that do not overlap when viewed from above in the stacking direction.
[0142] Fig.10 is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction, Fig.11 Observed from the stacking direction Fig.10 Plan view of an all-solid-state battery. Fig.10 and Fig.11 In the all-solid-state battery shown, the adhesive sheet 50G is provided along the end surface of the insulating sheet 40A on the side close to the stacked body 10 .
[0143] The first adhesive sheet 51G is, for example, a circular ring-shaped adhesive sheet having an inner diameter larger than the outer diameter of the laminate 10. The second adhesive sheet 52G is, for example, a shape obtained by removing a portion of the first adhesive sheet 51G. The second adhesive sheet 52G is, for example, a shape obtained by removing a portion of the circular ring shape. The second adhesive sheet 52G is, for example, in the shape of a "C". Alternatively, the shape may be a shape obtained by removing a portion of a polygonal shape.
[0144] By providing the adhesive sheet 50G such as the all-solid battery 100G along the end surface of the insulating sheet 40A on the side close to the stack 10, it is possible to suppress the positional deviation in the in-plane direction of the stack 10. In addition, by fixing the vicinity of the stack 10 in the in-plane direction, it is easy to suppress the deterioration of the contact between the stack 10 and the collector 15, and it is easy to obtain the effect of suppressing the increase of the internal resistance and the decrease of the battery capacity.
[0145] Fig.12 is a cross-sectional view of an all-solid-state battery according to another embodiment of the present invention cut along the stacking direction, Fig.13 Observed from the stacking direction Fig.12 Plan view of an all-solid-state battery. Fig.12 and Fig.13 In the all-solid-state battery 100H shown in FIG. 1 , the shape of the stack 10H, the shape and arrangement of the insulating sheet 40H and the adhesive sheet 50H are different from those of the all-solid-state battery 100A. The shape of the stack 10H may also be Fig.13 A roughly quadrilateral as shown.
[0146] In the all-solid-state battery 100H, the insulating sheet 40H, for example, has a through hole H40 of a similar shape to that of the stack 10H. The insulating sheet 40H can be arranged at a greater distance from the stack 10 in the in-plane direction than the insulating sheet 40A. The insulating sheet 40H is arranged, for example, in a manner that overlaps with the entire area of the contour of the collector 15 when viewed from the z direction. The adhesive sheet 50H is arranged, for example, in a manner that a portion of it overlaps with the collector and a portion of it does not overlap with the collector 15 when viewed from the z direction. The adhesive sheet 50H is, for example, arranged only in the -y direction relative to the stack 10H. Therefore, the stack 10H is, for example, an area between the insulating sheet 40H and the collector 15 in the z direction, and is connected to the outer casing 20 in the ±x direction and the +y direction relative to the stack 10H.
[0147] The adhesive sheet 50H provided as in the all-solid-state battery 100H is located in the first direction relative to the stack 10H, and the inner peripheral end of the insulating sheet 40H is bonded to the collector 15. In this way, the all-solid-state battery can also be a structure in which a part of the inner peripheral end of the insulating sheet is bonded to the collector. Even with such a structure, the stack 10H and the outer body 20 are connected, which can suppress the rapid increase of the air pressure near the stack 10 in the outer body 20, and can suppress the reduction of the internal resistance.
[0148] In addition, all-solid-state batteries can also be Fig.14 The structure shown. Fig.14The number of adhesive sheets 50H in the all-solid batteries 100I, 100J, and 100K shown in (a), (b), and (c) is different from that in the all-solid battery 100H. In the all-solid batteries 100I, 100J, and 100K, for example, the first adhesive sheet and the second adhesive sheet each include a plurality of adhesive sheets that are separated from each other in different directions relative to the stacked body 10H.
[0149] The all-solid battery 100I also has an adhesive sheet 50H2 located in the +y direction relative to the stack 10H, the all-solid battery 100I also has adhesive sheets 50H3 and 50H4 located in the ±x directions relative to the stack 10H, and the all-solid battery 100K also has an adhesive sheet 50H2 located in the +y direction and adhesive sheets 50H3 and 50H4 located in the ±x directions relative to the stack 10H. In addition, in the all-solid batteries 100I, 100J, and 100K, the adhesive sheets 50H1, 50H2, 50H3, and 50H4 are shorter than the length of the side of the collector 15 overlapping with each adhesive sheet when viewed from the stacking direction, for example. Even if Fig.14 The all-solid batteries 100I, 100J, and 100K shown in the figure also have gaps formed at least in the area between the adhesive sheets, which can ensure the exhaust path of the gas, thereby suppressing the increase of the internal resistance. In addition, as long as the gap A is generated, the length of the adhesive sheets 50H1 to 50H4 can also be longer than the length of the side of the collector 15.
[0150] In addition, all-solid-state batteries can also be Fig.15 The structure shown. Fig.15 The shapes of the adhesive sheets of the all-solid batteries 100L, 100M, and 100N shown in (a), (b), and (c) are different from those of the above-mentioned all-solid batteries. In the all-solid batteries 100L, 100M, and 100N, the adhesive sheets 50L, 50L1, 50L2, 50La, 50Lb, 50Lc, and 50Ld have a curved portion w on the end surface of one side close to the stack 10H, respectively. The curved portion w is, for example, arranged in a manner parallel to the vertex of the stack 10H. In each of the all-solid batteries 100L, 100M, and 100N, when a plurality of adhesive sheets are provided, the plurality of adhesive sheets are arranged separately from each other.
[0151] In addition, all-solid-state batteries can also be Fig.16 The structure shown. Fig.16The shape of the insulating sheet of the all-solid-state batteries 100O, 100P, and 100Q shown in (a), (b), and (c) is different from that of the above-mentioned all-solid-state batteries. In the all-solid-state battery 100O, the insulating sheet 40O is, for example, in a U-shape when viewed from above in the z direction. The insulating sheet 40O overlaps with the full length of three of the four sides constituting the collector 15, and partially overlaps with one side when viewed from above in the z direction. The shape of the adhesive sheet 50L is, for example, similar to the insulating sheet 40O. The adhesive sheet 50L in the all-solid-state battery 100O is, for example, congruent in the first adhesive sheet and the second adhesive sheet. The adhesive sheet 50L overlaps with, for example, three of the four sides constituting the outer shape of the collector. In the all-solid-state battery 100O, the stack 10H is connected to the outer casing 20 via the gap A in the +y direction. The all-solid-state battery 100P includes two insulating sheets 40P1 and 40P2 spaced apart in the y direction and adhesive sheets 50L1 and 50L2 that bond the insulating sheets 40P1 and 40P2 to the collector 15, respectively. The insulating sheets 40P1, 40P2 and the adhesive sheets 50L1 and 50L2 extend, for example, in the x direction and are arranged in parallel. In the all-solid-state battery 100P, the stack 10H is connected to the outer casing 20 via the gaps in the ±x directions. The all-solid-state battery 100Q includes four insulating sheets 40P1, 40P2, 40Q1, and 40Q2 spaced apart from each other in the in-plane direction. The insulating sheets 40P1 and 40P2 are arranged, for example, in a manner that sandwiches the insulating sheets 40Q1 and 40Q2 in the y direction. The insulating sheets 40P1, 40P2, 40Q1, and 40Q2 are arranged, for example, in a manner overlapping the sides constituting the outer shape of the current collector 15. The all-solid-state battery 100Q, for example, further includes adhesive sheets 50L1, 50L2, 50Q1, and 50Q2. The adhesive sheets 50L1, 50L2, 50Q1, and 50Q2 are arranged, for example, in a manner overlapping one of the four sides constituting the current collector 15. As described above, in the all-solid-state batteries 100P and 100Q, the first adhesive sheet and the second adhesive sheet, for example, each include a plurality of adhesive sheets arranged at intervals from each other in different directions relative to the stack 10H.
[0152] Even the above Figures 4 to 16 The all-solid-state battery of the modified example shown can also be used with Figure 1 to Figure 3 The same principle as the all-solid battery 100A shown above can suppress the decrease in the adhesion between the stack and the current collector. This can suppress the increase in internal resistance without using a fastening member.
[0153] In addition, in the above example, a structure in which only one stack 10, 10H is provided in one all-solid battery is shown, but a plurality of stacks may also be provided in one all-solid battery. In an all-solid battery, when a plurality of stacks are provided, the plurality of stacks are arranged, for example, in the in-plane direction. In addition, the plurality of stacks are connected to the outer casing 20, respectively. The connecting mechanism between the stack and the outer casing 20 can adopt the same mechanism as in the above example, for example, a gap A is formed. In addition, it may also be a structure in which a plurality of stacks are connected. In addition, the stack is not limited to a circle or a quadrilateral, and may be formed in any shape. In addition, the shape of the gap A when viewed from the stacking direction is not limited to a straight line, and may also be a curved shape. In addition, it may also be provided with a fixing belt in a manner that is further bonded to the outer side of the stacking direction of the positive electrode collector 15A and the negative electrode collector 15B of the above-mentioned all-solid battery. In addition, it may also be provided with a fastening member that presses and tightens the all-solid battery in the stacking direction. As a fastening member, for example, a metal plate, a bolt and a nut may be used. Specifically, the outer casing of the all-solid-state battery may be sandwiched between metal plates, and the four corners of the metal plates may be fastened with bolts and nuts to constrain the outer casing.
[0154] The above-described multiple embodiments may be implemented in combination as appropriate within the scope of the gist of the claims.
[0155] [Example]
[0156] Hereinafter, examples of the present invention will be described. However, the present invention is not limited to the following examples.
[0157] [Example 1]
[0158] As Example 1, make Fig. 9 The all-solid-state battery shown in (b) was prepared and the battery characteristics were evaluated. Specifically, Example 1 was carried out by the following means.
[0159] First, a laminated body in which a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer were laminated in this order was produced by a powder molding method in the following manner.
[0160] A lower punch with a diameter of 9.99 mm was inserted from the lower side of the through hole of the resin holder having a through hole with a diameter of 10 mm in the center. Next, Li2ZrCl6, which will become the solid electrolyte layer, was put in from the upper side of the through hole. Next, an upper punch with a diameter of 9.99 mm was inserted from the upper side of the through hole, and a press was used to press at a pressure of 5 kN to form a solid electrolyte layer with a thickness of 0.3 mm.
[0161] Next, the upper punch was temporarily removed, and a powder obtained by mixing 0.7 g, 0.35 g, and 0.03 g of LCO-solid electrolyte, which would become a positive electrode active material layer, with Li2ZrCl6 and carbon black was used. Next, the press was used again to press at a pressure of 5 kN to form a positive electrode active material layer with a thickness of 0.05 mm on the solid electrolyte layer.
[0162] Next, the lower punch was temporarily removed and the LTO-solid electrolyte mixture that would become the negative electrode active material layer was put in. As the LTO-solid electrolyte mixture, 0.55 g, 0.4 g, and 0.05 g of powders of LTO, Li2ZrCl6, and graphite were mixed using an agate mortar. Next, the press was used again to pressurize at a pressure of 5 kN to form a laminate with a thickness of 0.4 mm, in which a negative electrode active material layer with a thickness of 0.05 mm was provided on the lower side of the laminate of the positive electrode active material layer and the solid electrolyte layer.
[0163] Next, an insulating sheet and an adhesive sheet were produced.
[0164] Specifically, first, a 100 μm thick PET sheet of Lumirror H10 (manufactured by Toray Industries, Ltd.) was prepared as an insulating film; and two double-sided tapes (product number: HJ-3160W, manufacturing company name: Nitto Denko Corporation) having the same shape (same thickness and top view shape) as the insulating film were prepared as adhesive films.
[0165] Next, a Pinnacle knife (Pinnacle is a registered trademark) was used to form a circular through hole with an inner diameter of 11 mm at the center of the insulating film when viewed from above, thereby producing an insulating sheet. In addition, a through hole of the same shape was formed at the same position as the through hole in one of the two double-sided tapes, thereby forming a first adhesive sheet. In addition, a through hole of the same shape was formed at the same position as the through hole in the other double-sided tape, and a hole was formed through the center of the circle of the through hole to form a gap parallel to the side extending in the length direction of the double-sided tape and a gap extending in the short side direction, thereby forming a second adhesive sheet. That is, a through hole located at the center when viewed from above and four holes extending from the midpoints of the four sides toward the center of the circle of the through hole were formed in the double-sided tape, thereby producing an adhesive sheet. The insulating sheet was clamped by the first adhesive sheet and the second adhesive sheet in a manner that the respective through holes overlapped, thereby producing an insulating unit 45 having adhesive sheets provided on the main surfaces of both sides of the insulating sheet.
[0166] Next, the electricity storage element was assembled.
[0167] First, leads were joined to the positive electrode collector and the negative electrode collector on the outer sides of the positive electrode collector and the negative electrode collector in the stacking direction by ultrasonic welding. A sealed aluminum tab was used as the lead.
[0168] Next, the insulating sheet is bonded to the positive electrode collector via the first adhesive sheet. Next, the laminate is placed in the through hole using tweezers. Next, the insulating sheet is bonded to the negative electrode collector via the second adhesive sheet. Thus, the laminate is formed to be connected to the outside through the gap defined by the negative electrode collector, the second adhesive sheet, and the insulating sheet in the storage element.
[0169] Next, the obtained electric storage element was housed in an outer casing. As the outer casing, an aluminum laminate bag was used.
[0170] Next, heat seal is performed on all openings except one of the openings of the outer body 20. Then, the remaining opening is heat sealed while evacuating the interior of the outer body 20. By heat sealing while evacuating the interior, the outer body 20 can be sealed with less gas and moisture in the storage space K.
[0171] [Comparative Example 1]
[0172] As Comparative Example 1, a fully solid battery was produced in the same manner as in Example 1 except that no holes other than the through holes were formed in the second adhesive sheet. That is, in the fully solid battery of Comparative Example 1, the laminate was enclosed in a space surrounded by the positive electrode collector, the first adhesive sheet, the insulating sheet, the second adhesive sheet, and the negative electrode collector, and the laminate was not connected to the outer casing.
[0173] (Battery capacity test)
[0174] The all-solid batteries of Example 1 and Comparative Example 1 were subjected to a battery characteristic test. Specifically, the all-solid battery was placed in a thermostatic chamber at 25°C, and the charge and discharge characteristics were calculated using a charge and discharge machine SD8 (manufactured by Hokuto Denko Co., Ltd.). First, as a charging test, constant current charging was performed at 0.05C until the battery voltage reached 2.8V, followed by constant current charging until the current density reached 0.01C, followed by constant voltage charging until the current density reached 0.01C. Then, as a discharge test, constant current discharge was performed at 0.05C until the battery voltage reached 1.3V.
[0175] (Internal resistance)
[0176] The internal resistance (AC resistance) after the battery capacity test of the all-solid batteries of Example 1 and Comparative Example 1 was measured. The internal resistance was measured using a battery tester BT3563 (manufactured by HIOKI Electric Co., Ltd.).
[0177] Fig.17 The charge and discharge curves of Example 1 and Comparative Example 1 are shown. Table 1 shows the discharge capacity and internal resistance of Example 1 and Comparative Example 1. Fig.18 is a diagram showing the state of the all-solid-state battery after the battery capacity test and the internal resistance test. Fig.18 (a) Fig.18 (b) shows the appearance of the all-solid-state battery of Example 1 and Comparative Example 1, respectively. In Comparative Example 1, it was confirmed that gas accumulation occurred near the stacked body which was circular in plan view and surrounded by the insulating unit. On the other hand, in Example 1, the gas accumulation occurred in Comparative Example 1 was not confirmed.
[0178] In Example 1, the discharge capacity is large and the AC resistance is small compared with Comparative Example 1. Fig.18 Gas accumulation was confirmed in the test results, and it is believed that the gas was sealed together with the stack during assembly, or that the gas was generated due to the reaction of water near the stack with the solid electrolyte, the adhesion between the stack and the collector was reduced, the internal resistance increased, and the discharge capacity was small. In addition, in Comparative Example 1, the charging capacity was larger than the discharging capacity, so it is believed that the gas generated during the charging (and discharging) process has a greater impact than the gas sealed together with the stack during assembly of the storage element.
[0179] In the above-described Example 1, by forming the gaps so as to communicate between the stacked body and the outer casing, the all-solid-state battery is not pressurized from the outside in the stacking direction, and thus an increase in internal resistance can be suppressed and a high discharge capacity can be obtained.
[0180] [Table 1]
[0181] Example 1 Comparative Example 1 Discharge capacity(mAh) 0.65 0.03 Internal resistance (Ω) 319 2128
[0182] [Example 2]
[0183] The all-solid-state battery is pressurized and fastened in the stacking direction by a fastening member. In addition, the all-solid-state battery is made and the characteristics are evaluated by the same means as in Example 1. The pressurization of the fastening member is performed by applying a tightening torque of 1Nm to the four corners (the measured value is 200kgf). Specifically, in Example 2, the outer body is clamped by a metal plate via a bakelite board, and the four corners of the metal plate are fastened and constrained by bolts and nuts. Here, as a metal plate, a metal plate whose size in the in-plane direction is larger than that of the outer body is used.
[0184] [Comparative Example 2]
[0185] The all-solid-state battery was prepared and its characteristics were evaluated in the same manner as in Comparative Example 1, except that the all-solid-state battery was clamped by a clamping member while being pressed in the stacking direction.
[0186] After measuring the battery characteristics, when the fastening member was removed from the all-solid-state battery, gas accumulation was confirmed near the stack in Comparative Example 2, but no such gas accumulation was confirmed in Example 2. Therefore, in Example 2, it was confirmed that the gas near the stack could be discharged through the gap connecting the stack and the outer casing. Fig.19 Table 2 shows the charge and discharge curves of Example 2 and Comparative Example 2, and Table 2 shows the discharge capacity and internal resistance of Example 2 and Comparative Example 2. In Comparative Example 2 using a fastening member, the discharge capacity is improved compared to Comparative Example 1, but the discharge capacity is smaller than that of Example 1 and Example 2. In addition, the internal resistance of Example 2 is smaller than that of Comparative Example 2.
[0187] It is believed that the reason why the discharge capacity in Comparative Example 2 is smaller than that in Examples 1 and 2 and the reason why the internal resistance is larger than that in Example 2 is that the gas sealed together with the stack during assembly and the gas generated by the reaction between the solid electrolyte and water during charging reduce the adhesion between the stack and the collector.
[0188] [Table 2]
[0189] Example 2 Comparative Example 2 Discharge capacity(mAh) 0.65 0.52 Internal resistance (Ω) 199 236
[0190] [Example 3-1]
[0191] A full solid-state battery was produced by the same method as in Example 1 except that the thickness T51 of the first adhesive sheet was set to 50 μm and the thickness T52 of the second adhesive sheet was set to 50 μm.
[0192] [Example 3-2 to Example 3-6]
[0193] A full solid-state battery was produced in the same manner as in Example 3-1 except that the thickness T40 of the insulating sheet, the thickness T51 of the first adhesive sheet, and the thickness T52 of the second adhesive sheet were changed.
[0194] The conditions regarding the thickness T40 of the insulating sheet, the thickness T51 of the first adhesive sheet, and the thickness T52 of the second adhesive sheet in each embodiment, the ratio T51 / T52 of the thickness T51 of the first adhesive sheet to the thickness T52 of the second adhesive sheet, the ratio T52 / T51 of the thickness T52 of the second adhesive sheet to the thickness T51 of the first adhesive sheet, and the ratio T40 / T45 of the thickness T40 of the insulating sheet to the thickness T45 of the insulating unit are summarized in Table 3.
[0195] In addition, the discharge capacity and internal resistance of the all-solid batteries of Examples 3-1 to 3-6 were measured by the same method as in Example 1. These measurement results are also summarized in Table 3.
[0196] [Table 3]
[0197]
Claims
1. An all-solid-state battery, in, include: an outer casing; and The outer casing includes: a laminated body, which is sequentially laminated with a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer; a positive electrode collector and a negative electrode collector sandwiching the laminated body in the stacking direction; an insulating sheet, which is located between the positive electrode collector and the negative electrode collector and is located in the in-plane direction relative to the laminated body; a first adhesive sheet, which is located between the insulating sheet and the positive electrode collector and bonds the insulating sheet and the positive electrode collector at least in part; and a second adhesive sheet, which is located between the insulating sheet and the negative electrode collector and bonds the insulating sheet and the negative electrode collector at least in part, The stacked body is in communication with the outer body.
2. The all-solid-state battery according to claim 1, wherein: At least one gap is formed in the insulating unit composed of the first adhesive sheet, the insulating sheet, and the second adhesive sheet, The stacked body and the outer body are in communication with each other via the gap.
3. The all-solid-state battery according to claim 2, wherein: The gap is formed in at least one of the first adhesive sheet and the second adhesive sheet.
4. The all-solid-state battery according to claim 2, wherein: Two gaps are formed in the insulating unit. The two gaps are provided at positions where they do not overlap when viewed from above in the stacking direction.
5. The all-solid-state battery according to claim 2, wherein: Four gaps are formed in the insulating unit. The four gaps are provided at positions that do not overlap when viewed from above in the stacking direction.
6. The all-solid-state battery according to claim 2, wherein: The width of the gap is smaller than the minimum width when the stacked body is viewed from above in the stacking direction.
7. The all-solid-state battery according to claim 1, wherein: The first adhesive sheet and the second adhesive sheet are provided along an end surface of the insulating sheet on a side close to the laminate.
8. The all-solid-state battery according to claim 2, wherein: The gap is formed at a position where the first adhesive sheet, the insulating sheet, and the second adhesive sheet overlap each other when viewed in a plan view from a stacking direction.
9. The all-solid-state battery according to claim 1, wherein: The first adhesive sheet includes a plurality of adhesive sheets arranged at intervals from each other in different directions relative to the laminate. The second adhesive sheet includes a plurality of adhesive sheets disposed at intervals from each other in different directions relative to the laminate.
10. The all-solid-state battery according to claim 1, wherein: The distance between the positive electrode collector and the negative electrode collector in a region overlapping with the first adhesive sheet is smaller than the distance between the positive electrode collector and the negative electrode collector in a region overlapping with the laminate.
11. The all-solid-state battery according to claim 1, wherein: The first adhesive sheet and the insulating sheet surround the laminate in the in-plane direction. When viewed from the stacking direction of the stack, the shape of the inner periphery of the insulating sheet on the side close to the stack is similar or congruent to the shape of the inner periphery of either the first adhesive sheet or the second adhesive sheet on the side close to the stack.
12. The all-solid-state battery according to claim 1, wherein: The first adhesive sheet, the second adhesive sheet, and the insulating sheet surround the laminate in the in-plane direction. When viewed from the stacking direction of the stacked body, a dimension of the inner periphery of the stacked body surrounded by the first adhesive sheet and the second adhesive sheet is less than a dimension of the inner periphery of the stacked body surrounded by the insulating sheet.
13. The all-solid-state battery according to claim 1 or 2, wherein: The relationship between the thickness T40 of the insulating sheet and the total thickness T45 of the insulating sheet, the first adhesive sheet, and the second adhesive sheet satisfies the following formula [1]: 0.3≤T40 / T45≤0.96……[1].
14. The all-solid-state battery according to claim 13, wherein: The ratio T51 / T52 of the thickness T51 of the first adhesive sheet to the thickness T52 of the second adhesive sheet satisfies the following equation [2]: 0.15≤T51 / T52≤7……[2].
15. The all-solid-state battery according to claim 13, wherein: The thickness T51 of the first adhesive sheet is 4 to 110 μm.
16. The all-solid-state battery according to claim 13, wherein: The thickness T52 of the second adhesive sheet is 4 to 110 μm.
Citation Information
Patent Citations
Solid lithium secondary battery and method for manufacturing the same
JP2011159635A
Electrical element and method of manufacturing electrical element
JP2015076182A